Sistem Informasi Pendataan Barang Produksi Pameran Berbasis Web Pada PT Citra Shalos Kreasindo - Ahmad Baihaqi; Maulana Fansyuri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT Chitra Shalos Kreasindo is a company engaged in Exhibition or Exhibition that makes production such as booth, satellite, exterior and interior with production goods such as plywood, nails, melamine, and paint and other production goods. As for the problems that occur in the system that is currently running, namely for processing incoming and outgoing goods data, stock data is recorded in the ledger according to travel documents, notes, and receipts. Which contains how many items go in and out for production and inventory data collection is only recorded on a piece of paper and then it is copied back to the computer by the office, so that sometimes it has difficulty in calculating goods and to get information on stock items has difficulty sometimes the information that given is not in accordance with the availability of existing goods. The purpose of this research is to create a Goods Data Collection Information System, which can manage incoming and outgoing goods, stock of goods, with a WEB-based PHP programming language using the Extreme Programming method. The information system that has been generated in this design can manage incoming and outgoing goods data, generate stock data, by printing the report